Comparison of Clinical Characteristics of Pulmonary Tuberculosis Patients with and without Diabetes Mellitus at Dr. Soetomo Hospital - Idwar, Fadiah Dini Putri; Wahyunitisari, Manik Retno; Wironegoro, Rio; Rosyid, Alfian Nur (Indonesian Journal of Tropical and Infectious Disease, 2025)
Tuberculosis (TB) is a transmissible infectious condition attributable to Mycobacterium tuberculosis. Common symptoms of tuberculosis include a persistent cough lasting more than two weeks, fever, fatigue, malaise, and unintended weight loss. These symptoms may become more severe in individuals with co-infected Diabetes Mellitus (DM) due to impaired immunity. In 2021, approximately 400,000 people were reported to have TB-DM. Active TB can disrupt glucose tolerance, contributing to TB-DM2. Studies indicate this combination affects disease progression and treatment outcomes from both patients. This study employed an observational design with descriptive and analytical approaches. The study utilized medical record data from individuals diagnosed with TB who were managed at Dr. Soetomo General Academic Hospital in 2023.  There were 245 total patients, comprising 151 TB without DM and 94 TB with DM cases. The analysis demonstrated a statistically significant difference in mean age between the two groups (p = 0.000). In both groups, the majority were male (69.5%; 63.8%). Cough was more frequent in TB with DM patients (p = 0.038). The most common systemic symptom in both groups was weight loss (70.9%; 63.8%). AFB and GeneXpert MTB/RIF assays results showed no significant differences in between. However, significant differences were found in leukocyte, ALT, AST, and BUN levels (p = 0.001; 0.004; 0.019; 0.007). Radiological examinations showed no significant differences. TB patients with and without DM differ significantly in age, symptoms, and several laboratory parameters, suggesting that comorbidity may influence TB characteristics and clinical presentation.